Esterified Lignin from Construction and Demolition Waste (CDW) as a Versatile Additive for Polylactic‐Acid (PLA) Composites—The Effect of Artificial Weathering on its Performance. Issue 8 (11th June 2022) - Anugwom, Ikenna; Lahtela, Ville; Hedenström, Mattias; Kiljunen, Samantha; Kärki, Timo; Kallioinen‐Mänttäri, Mari
Abstract: Demand for sustainable packaging and building materials has increased the need for biobased additives. Biocomposites can often be exposed to different weather conditions and UV irradiation. Thus, additives to prevent the negative impact of weathering are generally added to composites. This study aims to evaluate using esterified lignin as an additive against weathering effects in polylactic‐acid (PLA) composites. Lignin is extracted from construction and demolition waste (CDW) wood using a deep eutectic solvent then esterified and tested as an additive in the fabrication of bio‐based composites. For comparison, lignin from birch is used as a raw material for an additive. Esterification is confirmed by solid‐state NMR analysis. Samples are exposed to artificial weathering for 700 hours and their impact strength and color change properties are measured. The results indicate that esterified lignin from CDW (CDW e‐lignin) as an additive protects the biocomposite from the weathering impact. The sample containing the CDW e‐lignin as an additive suffers only a 4.3% of reduction of impact strength, while the samples that contain commercial additives lose clearly more of their impact strength (from 23.1% to 61.1%). Based on the results CDW e‐lignin is a good additive to prevent weathering. As a conclusion, the esterified lignin from CDW, is a versatile additive for composite production. Abstract : Valorization for construction and demolition waste wood extracted lignin into a multi‐purpose additive for the fabrication of polylactic‐acid‐based wood composite is reported.